PERGERAKAN NILAI AKTIVA BERSIH (NAB) BERDASARKAN EVALUASI KESALAHAN METODE DOUBLE EXPONENTIAL SMOOTHING PADA REKSA DANA BNI-AM DANA LANCAR SYARIAH - Muhammad Noor Arridho; Kusrini Kusrini; Muhammad Rudyanto Arief (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2022)
Mutual funds are a place to raise public funds managed by legal entities which are then invested in se-curities in the form of stocks, bonds and money markets. In essence, investing can increase welfare in the future. However, the interest of the Indonesian people in investing is relatively low. Along with the devel-opment of mutual fund technology, it has become known to the wider community through the presence of capital market service application providers. although, mutual funds have a small risk, as capital increas-es the risk increases. In this study, the researcher predicts the movement of net asset value (NAV) in the BNI-AM Dana Lancar Syariah mutual fund using the Double Exponential Smoothing method with 1 varia-ble to give preference in minimizing investment risk.. Predictions were made based on historical data for the period from January to March 2022 and an evaluation of the MAPE prediction error of 0.0107% and MAD 0.171248 using an alpha weighting of 0.4.